Racial politics, Latin@ youth, and teacher education. Issue 2 (3rd April 2019) - Bondy, Jennifer M.; Braunstein, Lauren B.
ABSTRACT: Teacher educators concerned with creating equitable classrooms for Latin@ youth should attend to how racial and national politics affect this group of students. Latin@ youth face particular forms of marginalization that hold implications for pre-service teacher education curriculum and pre-service teacher preparation. Teacher educators committed to social justice should focus on how they equip prospective teachers to explore emotions of racist nativism, integrate multiple perspectives into the classroom, and discern how pre-service teachers understand culture. The questions raised by Latin@ youth experiences challenge what it means to prepare teachers in classrooms marked by increasing cultural pluralism.